The evaluation of homemakers’ knowledge and perception on home-based commercial food: malaysia experience - Abu Bakar, Ibrahim; Zakaria, Zahidatul Farihah; Mohd Shahizi, Nor Syamimi (Asian Scholars Network, 2025)
Abstract: Home-based commercial food is highly popular among Malaysian as it offers great convenience even though its cleanliness and safety are doubtful. This study evaluated homemakers’ knowledge and perception on the cleanliness and safety of home-based commercial food toward family holistic well-being. A total of 439 respondents were structured randomly recruited from all states of Malaysia. Respondents were required to complete a set of questionnaires comprising of three sections: sociodemographic information, level of knowledge of home kitchen cleanliness and perception of commercial home-based food. To assess the level of knowledge about home kitchen cleanliness, a scoring system was implemented in each question was assigned a score between 1 and 6 with total score of 178. Maximum of total score obtained was divided by the maximum possible score and then converted into percentage value. Score below 50% reflects poor level of knowledge, while scores between 51 to 70% indicate an average understanding. A score ranging from 71 to 85% represents good knowledge and score above 86% signify an excellent level of knowledge. For the perception of commercial home-based food, a set of question consisted of three options of answer consisting of agree, partially agree and disagree. The findings revealed that over half of the participants demonstrated excellent knowledge of home kitchen cleanliness. A statistically significant difference (p-value<0.05) in knowledge levels was observed based on marital status, kitchen size and involvement in home-based food business. However, no significance differences (p-value>0.05) were found in relation to gender, race and educational background. Additionally, more than 70% of respondents agreed that preparing of commercial food at home is appropriate, suggesting a growing acceptance of home-based food business in the community, The findings of this study may be utilized by the Ministry of Health Malaysia in developing evidence-based policies and regulatory frameworks for home-based commercial food.